ANALYSIS OF THE COMPOSITE STOCK INDEX IN INDONESIA - Anggia Ramadhan; Dewi Mahrani Rangkuty; Gilang Irwanto (TRANSACTION: Journal of Taxation, Accounting, Management and Economics, 2024)
This research was conducted in Indonesia to analyze and understand the influence exerted by exchange rates and bank interest rates on the Indonesia Composite Index (IDX). The researcher used a causal method with a quantitative approach. The type of data used was secondary data obtained from the Bank Indonesia website. Data collection techniques included literature review and documentation. Data analysis techniques involved multiple linear regression tests, classical assumptions, and hypothesis testing. The research results indicate that exchange rates partially have a significant influence on IHSG, while bank interest rates do not have a significant impact on IDX. Simultaneously, both interest rates and exchange rates together significantly affect IDX in Indonesia. Meanwhile, interest rates and exchange rates have a very strong correlation with IDX, with a percentage of 84.98%, and the remaining 15.02% can be explained by other variables not examined. Suggestions can be made for investors to be more careful and thoroughly examine changes in bank interest rates, taking into consideration factors such as central government policies other than Bank Indonesia. This way, the interest rates set by banks, offering the highest interest rates, can be an alternative in decision-making.